If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.10 = 2x + 1 Reorder the terms: 1.10 = 1 + 2x Solving 1.10 = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1.10 + -2x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 1.10 + -2x = 1 + 0 1.10 + -2x = 1 Add '-1.10' to each side of the equation. 1.10 + -1.10 + -2x = 1 + -1.10 Combine like terms: 1.10 + -1.10 = 0.00 0.00 + -2x = 1 + -1.10 -2x = 1 + -1.10 Combine like terms: 1 + -1.10 = -0.1 -2x = -0.1 Divide each side by '-2'. x = 0.05 Simplifying x = 0.05
| 2(y-3)=34 | | 4-8=4x-1 | | y=15m^2-10m-25 | | -12r^2+4=13r | | in(8x)=5.5 | | 3(5-2)=y | | -81-6x=-18+3x | | (5z+6)(3-z)=0 | | -7(x+3)=-16-7a | | 3gh-4h= | | -(3-4m)=7-6m | | 2b-18= | | 8(2(2)+4)-3(3(2)-6)= | | (5x-2)(-5x-4)= | | 3(6-1)=11p-45 | | A^2(b-1)-25(b-1)= | | 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= | | (k+1)x^2+(k+1)y^2+2kx+2ky+2y+4k+3=0 | | .25x-5+171=x | | 20/12=50/x | | 3(-5)(2)+6(-5)+-5(3(2)-6)= | | 2x+3x+(2+6)=8 | | 7x-2=4x-2 | | y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 | | 5x+45-89=-90+41 | | 3+2p=7 | | -5(2(2)+7)+2(9)+5(-5)= | | 5(z-1)-20=0 | | Y=2ln(3x-1)-2 | | -10x^2-6x-12=0 |